Probiotics and Gut Microbiota in Obesity: Myths and realities of a New Health Revolution (2022)
Obesity and its comorbidities are humans’ most prevalent cardio-metabolic diseases worldwide. Recent evidence has shown that chronic low-grade inflammation is a common feature in all highly prevalent chronic degenerative diseases. In this sense, the gut microbiota is a complete ecosystem involved in different processes like vitamin synthesis, metabolism regulation, and both appetite and immune system control. Thus, dysbiosis has been recognised as one of the many factors associated with obesity due to a predominance of Firmicutes, a decrease in Bifidobacterium in the gut, and a consequent short-chain fatty acids (SCFA) synthesis reduction leading to a reduction in incretins action and intestinal permeability increase. In this context, bacteria, bacterial endotoxins, and toxic bacterial by-products are translocated to the bloodstream, leading to systemic inflammation. This review focuses on gut microbiota composition and its role in obesity, as well as probiotics and prebiotics benefits in obesity.